Influence of Salinity Levels on Seedling Parameters Of Different Tomato Genotypes (Bangladesh Journal of Botany, 2023)
In the present study, 50 genotypes of tomatoes were tested in the roll towel method using seven levels of salt concentration from 0 to 120 mM of NaCl with an interval of 20 mM at laboratory conditions. Results showed that out of 50 genotypes, only 38 tomato genotypes germinated under a moderate salinity level of 80mM NaCl. The highest seedling fresh and dry weights were observed in LE-14 (0.271 and 0.045, respectively) under moderate salinity level which were on par with the genotypes LE-1, LE-1020, CLNR 2123, H24, IIVR88783 and LE-411. The highest fresh and dry seedling tolerance index were observed in IIVR-88783 (94.3 and 104.7) with an 80mM salinity level, which was on par with the genotypes, LE-1, LE- 1020, Arka Abhay, CLNR 2123, EC 164677, EC164838, EC164863, EC326146, IIVR 88783, IIVR EC 2494, IIVREC2798, LCR 2, LE-14, Pb-Rathak, Punjab Bagkoa and Punjab Bas with a moderate salinity level of 80 mM of NaCl. The genotypes LE-14, LE-1020, LE-1, LE-411, CLNR2123, H-24, IIVR-88783 and IIVR-EC2494 were found to be superior over 38 genotypes with the seedling characters.Bangladesh J. Bot. 52(2): 307-314, 2023 (June)